Indonesia's Policy in Addressing Marine Debris - Uly Maria Ulfah; Widodo, Widodo; Budiman Djoko Said; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (CV. AFDIFAL MAJU BERKAH, 2023)
Marine debris is a serious global environmental problem that affects the sustainability of marine ecosystems and human health. This research aims to analyze the threats posed by marine debris, such as its impact on marine life, ecosystems, and economies, as well as discuss Indonesia's policies in addressing the issue. The study aims to analyze the threats of marine debris to marine life, ecosystems, and economies, and identify the main sources of plastic waste in the ocean. This research utilizes secondary data analysis and literature review as research methods. The results show that marine debris has significant impacts on marine organisms and economic sectors. Indonesia's policies include improved waste management and increased public awareness. This research provides insights and recommendations for maintaining the sustainability of Indonesia's marine environment. In conclusion, this research highlights the importance of comprehensive policies and coordinated actions in addressing the issue of marine debris. Prevention efforts, proper waste management, and public awareness of the importance of maintaining the cleanliness of the ocean are key factors in reducing the negative impacts of marine debris. This research is expected to provide insights and recommendations for the government and other stakeholders in their efforts to preserve the sustainability of Indonesia's marine environment.